FROM THE HISTORY OF ORIENTAL ARCHEOGRAPHY IN DAGHESTAN - Bobrovnikov, Vladimir Olegovic (History, Archeology and Ethnography of the Caucasus, 2018)
The article analyzes prehistory of the Daghestani school of Oriental archaeography putting it into a wider context of post-colonial Soviet reforms. The author argues that academic source studies in the region is based of amateur area studies (kraevedenie). With the establishment of museums, circles and universities in the 1920s, Soviet Muslim elites were involved in copying, translating and studying documents and manuscripts from private and mosque libraries in the Arabic language and script. First archeographic expeditions were carried out by Muslim scholars and nascent local intelligentsia among whom Jadid modernists were influential. Academic source studies eventually appeared in Daghestan following the World War II under the influence of the Orientologist school from Leningrad. However, graduates of madrasas continued contributing in Oriental archaeography. In some respect, interests and views of Jadids and the first Soviet Orientologists close to them influenced the thematic repertoire of the largest state collection of manuscripts emerged from the middle of the 1920s at Institute of History, Archeology and Ethnography in Makhachkala. From the 1920s through the end of the 1980s the focus of field archeography was on original Daghestani writings and documents contrary to more general works and commentaries on Islamic law, dogmatics, ritual that dominated in the majority of mosque and private libraries. Moreover, Muslim modernists and their followers introduced into the research use classical monuments of the local Muslim historiography and documents dating back to the middle ages and early modern times.
Keywords: field Archeography; Oriental manuscripts and documents; area studies; Jadids; Cultural Revolution; Soviet modernization